2018
DOI: 10.1002/hlca.201800081
|View full text |Cite
|
Sign up to set email alerts
|

New and Scalable Access to Karrikin (KAR1) and Evaluation of Its Potential Application on Corn Germination

Abstract: Karrikin (KAR1), also named ‘karrikinolide’, was isolated in 2004 from smoke water and identified as a very potent germination stimulant as well as controlling early seedling development for a large variety of plant species. We reported herein an unprecedented and scalable synthesis of Karrikin (KAR1) based on an elegant and efficient 6‐endo‐dig cyclization. Moreover, we evaluated the effect of KAR1 on corn seeds germination, we carried out additional studies on the uptake of this butenolide into corn seeds, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
0
16
0
7
Order By: Relevance
“…Seed germination and early plant establishment play pivotal roles in crop productivity. Strigolactones stimulate the germination of parasitic weed seeds and it has been shown that these molecules can also induce lettuce, tomato and wild oat seed germination . We next evaluated the effect of our synthetic molecules on the germination of untreated corn and sunflower seed populations under cold stress.…”
Section: Resultsmentioning
confidence: 99%
“…Seed germination and early plant establishment play pivotal roles in crop productivity. Strigolactones stimulate the germination of parasitic weed seeds and it has been shown that these molecules can also induce lettuce, tomato and wild oat seed germination . We next evaluated the effect of our synthetic molecules on the germination of untreated corn and sunflower seed populations under cold stress.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] ¾hnlich wie bei Auxin wird die Entwicklung von synthetischen Strigolacton-Analoga entscheidend sein, um sowohl ihre biologische Relevanz zu verstehen als auch ihre Anwendung in der Landwirtschaft zu erforschen (Abbildung 1). [36][37][38][39][40] Racemisches GR24, das generell als Standard fürdie biologische Aktivität verwendet wird, konnte durch Formylierung eines achiralen Amids und Kupplung an das D-Ring-Chlorbutenolid relativ einfach produziert werden. [31][32][33][34][35] Wirbeteiligten uns durch die Entwicklung einer neuartigen, stereoselektiven Synthese von Strigolactonen:D iese nutzt Keteniminium als entscheidendes Zwischenprodukt fürd ie intramolekulare [2+ +2]-Cycloaddition zu einer C = C-Bindung,d ie im entsprechenden Cyclobutan-Iminium-Salz resultiert, das leicht zum Cyclobutanon hydrolysiert und weiter in das entsprechende Lacton und Lactam umgewandelt wird (Schema 1).…”
Section: Die Biologischen Eigenschaften Von Strigolactonenunclassified
“…Strigolactone werden in Pflanzen lediglich in Pikogramm-Mengen [30] produziert, daher ist die Verfügbarkeit synthetischer Strigolactone,a ber auch modifizierter/verbesserter Analoga von außerordentlicher Bedeutung.V erschiedene Gruppen haben Pionierarbeit bei der Herstellung von natürlichen und synthetischen Strigolactonen geleistet, im Besonderen die von Zwanenburg. [36][37][38][39][40] Auf ähnliche Weise wurden verschiedene Strigolactamderivate synthetisiert, die vergleichbare oder oft sogar verbesserte biologische Aktivität zeigen als die entsprechenden Lactone. [36][37][38][39][40] Racemisches GR24, das generell als Standard fürdie biologische Aktivität verwendet wird, konnte durch Formylierung eines achiralen Amids und Kupplung an das D-Ring-Chlorbutenolid relativ einfach produziert werden.…”
Section: Die Biologischen Eigenschaften Von Strigolactonenunclassified
See 2 more Smart Citations